Nationalist mobilization in the russian far east during the closing phase of the civil war - Sablin, Ivan (Vestnik Sankt-Peterburgskogo Universiteta / Istorija, 2017)
Three major factions in the Russian Civil War in the Far East engaged in nationalist mobilization coming up with different rhetorical tropes and images in the 1920-1922 period. The ultra-royalist faction led by Mikhail Konstantinovich Diterikhs, which in 1922 controlled the Provisional Priamur Government in Vladivostok, portrayed the Romanovs as redeemers who had ended the “dark age” of the Time of Troubles (1598-1613) and called for a new Zemskii Sobor to elect a Romanov Tsar for the sake of new redemption from the “foreign” Bolsheviks. The socialist faction of the Far Eastern Republic (FER), taken over by the Bolsheviks, focused on the grievances caused by the Romanovs’ policies and the clashes with Japan and stressed the future role of the Russians as the first nation of toilers to lead the global struggle for social justice. The popular monarchist faction, established by Grigorii Mikhailovich Semenov, tried to find a middle ground by emphasising the popular role in ending the Time of Troubles and agitating for an elected muzhik Tsar. The ultra-royalist and monarchist rhetoric failed to mobilize the people of the Far East who did not identify with the Eurocentric images of the past and rebuked the cooperation between the monarchists and Japan. The socialist claims that the Romanovs and the Japanese accounted for the degraded present proved more relevant in view of the regional historical narrative featuring a series of conflicts with East Asian states, while the economic rather than racial interpretation of the Japanese policies and the inclusive character of socialism did not alienate ethnic minorities from the socialist faction. Refs 22.